Optimization of performance and emission characteristics of CI engine fueled with waste safflower oil biodiesel and its blends - Singh D.K.; Tirkey J.V. (My University, 2025)
Biodiesel production represents a great opportunity to reduce marine and land pollution while incorporating circular economy principles into modern society. The objective of this research is to use the response surface methodology to evaluate the best engine performance and emission characteristics of safflower-based biodiesel and diesel mix dual-fuel Compression ignition engines. The optimization aims to increase brake power, and brake thermal efficiency, and reduce brake-specific fuel consumption and exhaust emissions. The independent input variables were biodiesel blending ratio, compression ratio, and engine load. The novelty of this study is to optimize the operating parameters of a dual-fuel compression ignition engine fueled with safflower biodiesel and diesel blend fraction. A total of 48 experimental trials were conducted. The oil output from safflower seed in the lab and the biodiesel yield obtained were 26% and 91%, respectively. RSM results predict the optimized magnitude of the biodiesel blending ratio, CR, and EL are B16.66, 16.68, and 12 kg, respectively. The optimal values for dependent parameters, that is, BP, BTE, BSFC, CO, UHC, CO2, and NO were 3.27 kW, 19.60%, 3.30 kg/kWh, 0.0006 (% vol.), 0.8 (ppm), 0.78 (% vol.), and 140.87 ppm, respectively. The cumulative composite desirability was found to be 0.5877. © 2022 Taylor & Francis Group, LLC.